ANALYSIS OF APPROACHES TO THE STUDY OF THE WORKS OF MAHMUD ZAMAKHSHARI - Saidjalolov Saidafzal (Web of Journals Publishing, 2025)
Maḥmūd Zamakhsharī is a great mufassir, mutakallim, jurist who came from Movarounnahr. When the scientific, cultural and economic situation in Mā Warāʾ al-Nahr was in decline, Maḥmūd Zamakhsharī served to revive and restore science with selfless scientists. Ten of his works are known today, and scientific researches on these works continue without stopping.
Keywords: Nuʿmān ibn Thābit, Maḥmūd Zamakhsharī, ibn Khallikān, Ḥājjī Khalīfah, Muḥammad ibn Idrīs ash-Shāfiʿī, Ru’ūs al-masā’il, Tāj al-tarājim, al- Aʻlām.